Persamaan Diferensial Bernouli - Marliza Syafitri (Jurnal Pustaka Cendekia Pendidikan, 2025)
A differential equation is an equation that contains the derivative of one or more of the independent variables. An ordinary differential equation contains only one independent variable, while a partial differential equation contains more than one variable. This article explains how to solve Bernouli's differential equation which is a first order differential equation and can be solved by the integral factor method.